Assessment of Reliability of Advanced Lipid Parameters for Premature Coronary Artery Disease in Young Indians: A Case-control Study - Rahul Patil; Sheetal Kudineerakatte; Vikrant Vijan; Dimpu Edwin (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Coronary Artery Disease (CAD) appears even in patients with normal level of conventional lipid parameters. But due to lack of specific guidelines on Indian population, involving detection of advanced lipid indices, has resulted in inadequate finding, management, and control of cardiovascular disease risks. This emphasises the need of advanced lipid indices for prediction of CAD at younger age. Aim: To evaluate the reliability of advanced lipid indices compared to conventional lipid parameters for diagnosis of CAD. Also, to determine the effectiveness of advanced lipid indices in screening young Indian for the risk of Premature CAD (PCAD). Materials and Methods: A case-control study was conducted at a tertiary care centre in Bengaluru, Karnataka, India, between January 2020 to January 2022. The study enrolled total 983 subjects which were divided into cases and controls. The estimation of usual lipid profile {Triglycerides (TG), High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), and Total Cholesterol (TC)} and advanced lipid parameters, oxidised LDL, Apolipoprotein A1 (Apo A1), lipoprotein (a), small density LDL (Sd-LDL), and Apolipoprotein B-100 (Apo B) was studied for each enrolled individual. These lipid parameters were used to calculate various lipid indices like Lipid Pentad Index (LPI), Lipid Tetrad Index (LTI), Atherosclerotic Index (AI), and Advanced Atherosclerotic Index (AAI); and TC/HDL ratio. Statistical analysis was performed using Chi-square test, Fisher’s-exact test, multivariate logistic regression, and Student’s t-test/Analysis of Variance (ANOVA) test. Results: Mean age of participants in case group was 32.31±5.42 years and in control group was 32.13±5.21 years. Among case group, 427 (88.04%) enrolled males had PCAD. In case group, total 45 (9.28%) had diabetes, 51 (10.51%) had family history of PCAD and 230 (47.42%) patients were smokers. The values of TC (p-value=0.009), LDL (p-value<0.001), Apo A1 (p-value<0.001), HDL (p-value<0.001) were significantly lower among cases compared to controls, lipoprotein (a) (p-value=0.04), Sd-LDL (p-value<0.001), TG (p-value<0.001) were significantly higher among cases compared to controls. Among the calculated lipid indices, the values of AI (p-value<0.001), LTI (p-value<0.001), LPI (p-value=0.001) and AAI (p-value=0.01) were significantly higher among cases as compared to controls. Conclusion: Advanced lipid indices are statistically more reliable than conventional lipid parameters. Newer advanced lipid indices are effective in screening young Indian individuals for the risk of PCAD.